FESTIVAL JOGOKALI: Resistensi Terhadap Penggusuran dan Gerakan Sosial-Kebudayaan Masyarakat Urban - Arianto, Andri (The Sociology of Islam, 2011)
This study discusses the symbolic resistance of urban poor who defend settlements in flood plains of Strenkali Wonokromo Surabaya from the threat of eviction by using the media arts and culture as a form of social movements. Forced eviction of public housing by the state is a common phenomenon that occurs in big cities in Indonesia at present. However, the threat of evictions was not only by the state only but also with public opinion on their residential slums. Based on these phenomena, this study will conduct thick description of the process of using ethnographic methods approach. Through ethnographic methods, this study is to describe the social structure and culture of a society with emphasis on the exploration of the nature of a particular social phenomenon rather than testing hypotheses. The focus of ethnographic attempts to draw broad conclusions from a small thing, but that is composed of solid facts. The results of this study showed that the resistance to forced evictions is no solution by the flood plain of participatory times of strenkali Wonokromo through symbolic resistance to the use of media arts and culture in the form of a festival. Arts and cultural practices of the festival named Jogokali, a position statement of self-expression, opinion, and thoughts of urban poor who live in flood plains of strenkali who often do not experience oppression in hearing their aspirations. In addition, through the practice of the arts and culture, urban poor provide counterpart concepts can be proposed and formulated by the communities themselves to the country and want to introduce to the general public about the concept and its role for the wider community in conserving river. Kata Kunci: Community of Strenkali, eviction, Practice of artistic-culture, Hegemony, and Social movement